Pre-Service Teachers’ Tendencies and Perceptions towards Lifelong Learning - Pilli, Olga; Ahmet Sönmezler; Necla Göktan (European Journal of Social Science Education and Research, 2019)
Lifelong learning is very important for teachers to revise their responsibilities and roles for teaching. The foundation of lifelong learning relies on one’s personal desire to improve themselves and their learning skills. Lifelong learning is infinite and there are no boundaries for lifelong learning. There are couple of concepts for lifelong learning which helps people to organize their self-learning and lifelong learning skills. Some of these concepts include self-determination on what to learn and evaluate the validity of the information that is determined for learning, a viable method on how to successfully learn and finally the assessment of the progress in learning. The aim of this research study is to investigate the pre-service teachers` tendencies and competencies on the qualifications for lifelong learning. It also tries to find out whether these tendencies and competencies differ between various departments and gender. As a research approach, a survey method is administrated to the 2nd year students studying in various departments at the Faculty of Education in Girne American University in the fall semester of 2016-2017 academic year. The research data is obtained from “Lifelong Learning Tendency Scale” and “Lifelong Learning Competence Scale” which will be analysed with respect to various departments and gender. The results will provide comprehensive understanding of the pre-service teachers` lifelong learning skills. Based on the analysed results, proper recommendations will be provided to the pre-service teachers to refine deficiencies in this field which will hopefully help to illuminate the future of lifelong learners and their learning skills.
Keywords: Lifelong learning, student teachers, pre-service teachers, lifelong learning tendency, lifelong learning competency.